The Influence Between Brand Loyalty and Brand Equity on Behavioral Loyalty and Attitudinal Loyalty - Muh. Said; Asri Asri (Universitas Negeri Makassar, 2019)
The level of development of the competitive environment in marketing today is increasingly aligned with the era of the digital industry that is a marketing or promotional activity or product or brand by using digital media or the internet or it can be said that digital marketing is an institution that can attract consumers or potential customers quickly and can reach all potential areas. The purpose of this study was to determine the effect of brand loyalty on brand equity, the effect of brand equity on behavioral loyalty, and the effect of brand equity on attitudinal loyalty. The research method used is hypothesis testing. The study was conducted by distributing questionnaires to respondents. The determination of the population in this study was the strata 1 students of the Management Program of STIE Nobel Indonesia Makassar and the samples of this study were 100 respondents. The results showed that brand loyalty has a significant and positive influence on brand equity. Brand equity has a significant and positive direct effect on behavioral loyalty. Brand equity has a significant and positive direct effect on aititudinal loyalty.